An Efficient Algorithm for Computing Hypervolume Contributions - Bringmann, Karl; Friedrich, Tobias (Evolutionary computation, 2010)
The hypervolume indicator serves as a sorting criterion in many recent multi-objective evolutionary algorithms (MOEAs). Typical algorithms remove the solution with the smallest loss with respect to the dominated hypervolume from the population. We present a new algorithm which determines for a population of size with objectives, a solution with minimal hypervolume contribution in time ( log ) for > 2. This improves all previously published algorithms by a factor of for all > 3 and by a factor of for = 3. We also analyze hypervolume indicator based optimization algorithms which remove λ > 1 solutions from a population of size = μ + λ. We show that there are populations such that the hypervolume contribution of iteratively chosen λ solutions is much larger than the hypervolume contribution of an optimal set of λ solutions. Selecting the optimal set of λ solutions implies calculating conventional hypervolume contributions, which is considered to be computationally too expensive. We present the first hypervolume algorithm which directly calculates the contribution of every set of λ solutions. This gives an additive term of in the runtime of the calculation instead of a multiplicative factor of . More precisely, for a population of size with objectives, our algorithm can calculate a set of λ solutions with minimal hypervolume contribution in time ( log + ) for > 2. This improves all previously published algorithms by a factor of for > 3 and by a factor of for = 3.